PERCEIVED SOCIAL SUPPORT AND COPING STYLES AS MODERATORS FOR LEVELS OF ANXIETY, DEPRESSION AND QUALITY OF LIFE IN CANCER CAREGIVERS: A LITERATURE REVIEW - Veronika Duci; Izela Tahsini (European Scientific Journal, ESJ, 2012)
During the last decades there is a trend in cancer treatment towards giving care at home settings. This trend presents the caregivers, mainly family members, with many difficult and complex tasks. The aim of this study is to explore the impact of perceived social support and coping strategies employed to the levels of anxiety and depression, as well as to the perception for the quality of life to cancer caregivers through a systematic literature review. Perceived social support results in fewer mental health symptoms, like anxiety and depression, and better quality of life, but this is not supported by all the studies. Likewise, some coping strategies, like active coping, have been also considered as important factors influencing quality of life and symptoms of anxiety and depression. Although there are many studies in the area of cancer, the majority of them have the patient in focus. There are few studies focused in the caregiving experience. In an Albanian setting, to the researchers’ knowledge, there isn’t any other study that targets caregivers.